Development of an in vivo target‐engagement biomarker for TRPA1 antagonists in humans. (17th November 2016) - Buntinx, Linde; Chang, Lin; Amin, Aasim; Morlion, Bart; de Hoon, Jan
Abstract : Aim: To develop a non‐invasive, safe and reproducible target‐engagement biomarker for future TRPA1 antagonists in healthy volunteers. Methods: Dose finding ( n  = 11): 3%, 10%, and 30% cinnamaldehyde (CA) and placebo (= vehicle) was topically applied on the right forearm. One‐wayANOVA with post‐hoc Bonferroni was used to compare between doses. Reproducibility : 10% CA doses were topically applied during one visit on both arms ( n  = 10) or during two visits ( n  = 23) separated by a washout period of 7 days. CA‐induced dermal blood flow (DBF) was assessed by laser Doppler imaging (LDI) at baseline and at 10, 20, 30, 40 and 50 min post‐CA. Paired t ‐test was used to compare between arms or visits. Concordance correlation coefficient (CCC) was calculated to assess reproducibility. Data are expressed as percent change from baseline (mean ± 95% CI). Results: All three doses increased DBF compared to vehicle at all time‐points, with the maximum response at 10–20 min post‐CA. Dose response was found when comparing AUC0–50min of 30% CA (51 364 ± 8475%*min) with 10% CA (32 239 ± 8034%*min, P  = 0.03) and 3% CA (30 226 ± 11 958%*min, P  = 0.015). 10% CA was chosen as an effective and safe dose. DBF response to 10% CA was found to be reproducible between arms (AUC0–50min, CCC = 0.91) and visits (AUC0–50min, CCC = 0.83). Based on sample size calculations, this model allows a change in CA‐induced DBF of 30–50% to be detected between two independent groups of maximum 10–15 subjects with 80% power. Conclusions: Evaluation of CA‐induced changes in DBF offers a safe, non‐invasive and reproducible target‐engagement biomarker in vivo in humans to evaluate TRPA1 antagonists.